Four‐week nutritional audit of preterm infants born <33 weeks gestation. Issue 4 (11th December 2012) - McLeod, Gemma; Sherriff, Jill; Nathan, Elizabeth; Hartmann, Peter E; Simmer, Karen
Abstract Aim Preterm nutritional audits have previously been conducted using assumed milk composition. We audited protein and energy intakes in the first 28 days of preterm life using both assumed milk composition and milk analysis to assess their effect on weight gain and to determine if the recommended reasonable range of intakes were met. Methods Parenteral and enteral intakes and weight gain were recorded daily for infants (n = 63) born <33 weeks gestation, using assumed milk composition. Macronutrient composition was determined by milk analysis for a subset of infants (n = 36). Linear mixed models analysis was used to assess the influence of energy and protein intakes on weight gain. Results (Data median (range)): Infants (n = 63) gestation and birth weight were 30 (24–32) weeks and 1400 (540–2580) g, respectively. Macronutrient milk composition was variable: protein 16.6 (13.4–27.6) g/L, fat 46.1 (35.0–62.4) g/L, lactose 68.0 (50.9–74.8) g/L, energy 3074 (2631–3761) kJ/L. Intakes based on measured composition differed from assumed. Protein intake was significantly associated with weight gain. Compared to infants with longer gestations, those born <28 weeks gestation were fed lower volumes, were more reliant on parenteral nutrition, took an additional seven days to transition to fortified feeds and median weight gain velocity took a fortnight longer to reach targets. Conclusion Preterm milk composition is variable and routine fortification using assumed composition may result in inappropriate nutrition. Fortification regimens stratified by birth gestation may be necessary to achieve preterm nutrition and growth targets. Milk analysis is required for accurate nutritional audit.